Global Gene-expression Analysis of the Response of Salmonella Enteritidis to Egg White Exposure Reveals Multiple Egg White-imposed Stress Responses - Baron, Florence; Bonnassie, Sylvie; Alabdeh, Mariah; Cochet, Marie-Françoise; Nau, Françoise; Guérin-Dubiard, Catherine; Gautier, Michel; Andrews, Simon C.; Jan, Sophie (Frontiers in Microbiology, 2017)
Chicken egg white protects the embryo from bacterial invaders by presenting an assortment of antagonistic activities that combine together to both kill and inhibit growth. The key features of the egg-white anti-bacterial system are iron restriction, high pH, antibacterial peptides and proteins, and viscosity. Salmonella enterica serovar Enteritidis is the major pathogen responsible for egg-borne infection in humans, which is partly explained by its exceptional capacity for survival under the harsh conditions encountered within egg white. However, at temperatures up to 42 ˚C, egg white exerts a much stronger bactericidal effect on S. Enteritidis than at lower tempertaures, although the mechanism of egg-white-induced killing is only partly understood. Here, for the first time, the impact of exposure of S. Enteritidis to egg white under bactericidal conditions (45 ˚C) is explored by global-expression analysis. A large-scale (18.7% of genome) shift in transcription is revealed suggesting major changes in specific aspects of S. Enteritidis physiology: induction of egg-white related stress-responses (envelope damage, exposure to heat and alkalinity, and translation shutdown); shift in energy metabolism from respiration to fermentation; and enhanced micronutrient provision (due to iron and biotin restriction). Little evidence of DNA damage or redox stress was obtained. Instead, data are consistent with envelope damage resulting in cell death by lysis. A surprise was the high degree of induction of hexonate/hexuronate utilisation genes, despite no evidence indicating the presence of these substrates in egg white.